2018
DOI: 10.3832/ifor2754-011
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term natural regeneration after windthrow disturbances in Norway spruce forests in Bulgaria

Abstract: Norway spruce forests are among the forests most affected by natural disturbances in Europe. One of the key aspects is the regeneration of the disturbed areas, which is decisive for later forest development. We studied the natural regeneration after two windthrows that occurred 30 (1983) and 50 years ago (1962) in an old-growth forest over 150-year-old in the Parangalitsa Reserve and a recent windthrow (2001) in a 130-year-old single cohort forest in the Bistrishko branishte Reserve in Bulgaria. We set up stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…However, seed germination and seedling establishment were slow due to the improved levels of light conditions in small size gaps. Our finding disagrees with a comment of Tsvetanov et al (2018) that spruce regeneration might preserve their vitality under forest canopy for several years and then grow vigorously when light conditions improve after forest disturbance. Moving on, natural regeneration of larch species was statistically different from spruce in big size gaps across the studied two consecutive growing seasons after gap disturbance respectively.…”
Section: Effect Of Gap Disturbance On Natural Regeneration Dynamics Within Gaps Of Two Different Sizescontrasting
confidence: 99%
See 2 more Smart Citations
“…However, seed germination and seedling establishment were slow due to the improved levels of light conditions in small size gaps. Our finding disagrees with a comment of Tsvetanov et al (2018) that spruce regeneration might preserve their vitality under forest canopy for several years and then grow vigorously when light conditions improve after forest disturbance. Moving on, natural regeneration of larch species was statistically different from spruce in big size gaps across the studied two consecutive growing seasons after gap disturbance respectively.…”
Section: Effect Of Gap Disturbance On Natural Regeneration Dynamics Within Gaps Of Two Different Sizescontrasting
confidence: 99%
“…So, creating artificial gaps based on stand conditions has emerged as a widespread phenomenon to achieving forest regeneration and succession, including other management objectives (Kollár 2017;Lu et al 2018a). Disturbances that open gaps provide specific microenvironmental conditions in light, soil moisture, and temperature regimes, which often initiate regeneration processes and development (Yamamoto 2000;Tsvetanov et al 2018). Seedling establishment, survival, and growth exclusively depend on light (Kyereh et al 1999;Diaci et al 2008).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although salvage logging is often carried out for economic reasons, it is known to cause direct harm to regeneration and can thus negatively affect forest recovery (Bowd et al, 2021;Royo et al, 2016;Taeroe et al, 2019). Furthermore, the deadwood being removed could otherwise act as a regeneration substrate, especially for spruce, when sufficiently decayed (Bače et al, 2012;Priewasser et al, 2013;Tsvetanov et al, 2018), a microsite that protects seedlings from climate stress (Marangon et al, 2022), or as an obstacle for herbivores (Hagge et al, 2019;Kramer et al, 2014;Marangon et al, 2022). However, a meta-analysis by Leverkus et al (2021) found that post-disturbance salvage logging does not generally hinder forest regeneration, and in some cases, the soil perturbation caused by logging can promote the regeneration of pioneer species by reducing competition with ground vegetation (Ilisson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the species has long been economically extremely important [7]. Since the regeneration potential of this species is usually high (thanks to seed-producing survivors after disturbance and well-dispersing and germinating seeds), spruce trees often dominate in species composition of young post-disturbance forests [8]. At the same time, in disturbed forest areas, seeds of different species-especially light-demanding, are granted an opportunity to germinate and cover the open soil surface [9].…”
Section: Introductionmentioning
confidence: 99%